Financial Aid for Female Graduate Students, Researchers and Foreign Residents in Mexico, Over 35 Years Old - Mercado, Diana Arauz (Cultural and religious studies, 2017)
CONACYT in México has implemented in recent years three types of scholarships and different specific supports for women who wish to complete their professional training, based on the National Development Plan "Equal Opportunities". These are in first place, Support for mothers who are heads of household (Bachelor and technical formation of a third level) such as single, divorced, widowed or separated Mexican mothers. In second place, it is the program complementing an education, specialization, masters or PhD—through Scholarship grants for academic strengthening of indigenous women in CONACYT enrolled in graduate studies in Mexico or abroad and the third place the Young Talents Program. Those modalities have met their specific objectives (we will focus on the first type); however, the realities pertaining to the academic, scientific, work and life cycle of women in the XXI century go beyond marital statuses, motherhood, or any particular social statuses or being indigenous and this study motives the analysis of this matter in the country.